Las condiciones de riesgo en el territorio: un punto de partida de la extensión universitaria - Brenes-Maykall, Alice (2023)
The Universidad Nacional (UNA) -Costa Rica-, through its Programs, Projects and Activities (PPAA), promotes joint processes with society and the State, contributing to social transformation in response to the needs of the territories. According to DesInventar (2023), between 1970-2022, 85% of the registered disasters corresponds to hydrometeorological origin. The foregoing raises the question: How much does the spatial distribution of the extension PPAA coincide in relation to the impacts of disasters of hydrometeorological origin in the territories? Through a comparative exploratory exercise between two databases (2014-2021), the territories impacted by disaster are related to the presence of disaster risk management PPAAs, generating a map for better representation and spatial analysis. The recommendations suggest that tools such as DesInventar could be used so that the different academic instances prioritize those historically impacted country regions to direct their efforts.